The core readiness of Sleman Region community on mobile health implementation: a qualitative study - Septianingtyas, Adinda; Pertiwi, Ariani Arista Putri; Yuliandari, Kurnia Putri (Journal of Community Empowerment for Health, 2025)
Introduction: The innovation of healthcare technology has developed rapidly, including mobile health (mHealth). The success of mHealth implementation in community settings obtain influenced by core readiness factors, distinctly community needs towards mHealth. This study aims to explore the core readiness of the Sleman Region community on the use of mHealth, specifically the features needed and the determining aspects of acceptance.Methods: This study used a qualitative design and conducted in-depth interviews with 13 community members. Participants were chosen purposively by Public Health Centre with various characteristics from January-March 2020. The verbatim transcripts were analysed using the direct content analysis technique with peer debriefing.Results: There are five themes of core readiness that are identification of needs obtained feature needed, satisfaction and dissatisfaction when using existing applications, knowledge of mHealth potency including advantages and disadvantages, acceptance of aspects that determine the use of mHealth, and enthusiasm for future mHealth that including reasons whether using the application or not. Specifically, the following features needed in the community are health information, self-medication, online consultation, mapping of healthcare services, peer support group, health promotion, personal training, emergency, personal health record, and feature for specific groups. The eight determining aspects of mHealth influencing community acceptance are interface design, easiness, content delivery, cost, promotion, performance, safety, privacy, and sustainability.Conclusions: The findings indicate that the Sleman Region community stands ready to accept the implementation of mHealth based on core readiness exploration. These findings can become a consideration in the development of future mHealth applications.